2021
DOI: 10.5603/fhc.a2021.0009
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of ghrelin expression in various types of adrenal tumors

Abstract: Introduction. Ghrelin, originally isolated from the endocrine cells of the gastric mucosa, is also expressed in many peripheral tissues, including normal adrenals and adrenocortical tumors. It was shown that ghrelin stimulates proliferation and inhibits apoptosis of adrenocortical cells. In the current study, we compared ghrelin expression at the protein level in various adrenal tumors. We analyzed whether immunoreactive ghrelin could be considered as a potential marker for different types of adrenal tumors. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Ghrelin, a widely distributed peptide hormone, participates in a series of cancer progression (35); GHRL plays a vital role in carcinogenic potential, which was correlated with breast cancer, lung cancer, bladder cancer, and adrenal cancer (17)(18)(19)(20). There is an increasing evidence implicating an immunoregulatory role for ghrelin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghrelin, a widely distributed peptide hormone, participates in a series of cancer progression (35); GHRL plays a vital role in carcinogenic potential, which was correlated with breast cancer, lung cancer, bladder cancer, and adrenal cancer (17)(18)(19)(20). There is an increasing evidence implicating an immunoregulatory role for ghrelin.…”
Section: Discussionmentioning
confidence: 99%
“…found that ghrelin and its receptor (GHSR) were expressed in T cells and monocytes; ghrelin inhibited the expression of proinflammatory cytokines tumor necrosis factor alpha (TNF-a) and interleukin (IL)-6 and inhibited inflammatory reactions ( 12 ). It has been confirmed that the stomach was indeed not the only source of ghrelin ( 13 ); hypothalamus, hippocampus, pituitary gland, cortex, small intestine, and pancreas can also secrete a small amount of ghrelin ( 14 16 ), GHRL plays important roles in the development of tumors, and aberrant GHRL expression has been found in various cancers, such as breast cancer ( 17 ), lung cancer ( 18 ), bladder cancer ( 19 ), and adrenal cancer ( 20 ). At present, there were some researchers who found that ghrelin affects cancer cell proliferation, migration, and invasion through different signaling pathways ( 21 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin, a widely distributed peptide hormone, participates in a series of cancer progression [27] , GHRL plays a vital role in carcinogenic potential, which was correlated with breast cancer, lung cancer, bladder cancer, and adrenal cancer [17][18][19][20] . There is an increasing evidence implicating an immunoregulatory role for ghrelin.…”
Section: Discussionmentioning
confidence: 99%
“…Dixit et al found that ghrelin and its receptor (GHSR)were expressed in T cells and monocytes, ghrelin inhibited the expression of proin ammatory cytokines TNF-a and IL-6, and inhibited in ammatory reactions [12] . It has been con rmed that the stomach was indeed not the only source of ghrelin [13] , hypothalamus, hippocampus, pituitary gland, cortex, small intestine, and pancreas can also secrete a small amount of ghrelin [14][15][16] , GHRL plays important roles in the development of tumors, and aberrant GHRL expression has been found in various cancers, such as breast cancer [17] , lung cancer [18] , bladder cancer [19] , and adrenal cancer [20] . At present, there were some researchers who found that ghrelin affects cancer cell proliferation, migration, and invasion through different signaling pathways [21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…The detailed procedure for the preparation and staining of TMA sections was as previously described [ 28 ]. Briefly, after deparaffinization, the TMA section was rehydrated through a series of decreasing ethanol concentrations and subsequently washed in phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%